2008
DOI: 10.1128/jcm.01014-08
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bacterial and Yeast Species with the Bactec 9120 Automated System with Routine Use of Aerobic, Anaerobic, and Fungal Media

Abstract: Despite recent developments in microbiological biomolecular techniques, blood culture remains the most practical and reliable method in the diagnosis of bloodstream infections and one of the most important tools in the clinical microbiology laboratory, taking into account the role played by systemic infections as a major cause of mortality and morbidity, especially within the hospital environment. Various continuously monitoring blood culture systems are extensively used in order to increase the rapidity of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 22 publications
1
19
1
1
Order By: Relevance
“…The rationale for choosing Bactec MICF bottles for these experiments was that in experiments evaluating the general applicability of different commercial blood culture systems for detecting Candida spp., Bactec MICF bottles, which include supplements specifically adapted for the growth of fungi, were shown to be more sensitive and to detect Candida spp. faster than most other conventional blood culture media (4)(5)(6)(7)(8). This finding was confirmed by the results of our study, since for controls inoculated without antifungal agents, we found reduced median TTPs in MICF bottles compared to those in PAF bottles (21.1 h versus 24.4 h for C. albicans and 22.0 h versus 43.2 h for C. glabrata, respectively).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The rationale for choosing Bactec MICF bottles for these experiments was that in experiments evaluating the general applicability of different commercial blood culture systems for detecting Candida spp., Bactec MICF bottles, which include supplements specifically adapted for the growth of fungi, were shown to be more sensitive and to detect Candida spp. faster than most other conventional blood culture media (4)(5)(6)(7)(8). This finding was confirmed by the results of our study, since for controls inoculated without antifungal agents, we found reduced median TTPs in MICF bottles compared to those in PAF bottles (21.1 h versus 24.4 h for C. albicans and 22.0 h versus 43.2 h for C. glabrata, respectively).…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, some studies have evaluated the commercial Bactec system for its ability to detect Candida bloodstream infections. With this system, Bactec Mycosis IC/F (MICF) blood culture bottles, which are specifically adapted to the growth of Candida spp., were demonstrated to have a significantly shorter time to positivity (TTP) and a higher Candida detection rate than conventional (an)aerobic media (such as the Bactec Plus Aerobic F [PAF] and Bactec anaerobic bottles) (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Because diagnosis and treatment with antifungal agents tend to be delayed in such cases, the mortality rate is high (1,2). Part of the reason for this is that the estimated sensitivity of candidemia detection methods using standard aerobic and anaerobic blood culture bottles is only about 50% (3)(4)(5)(6). Blood culture media for mycobacteria, however, are more suitable for detecting fungi in vitro than these traditional media are (7).…”
Section: Introductionmentioning
confidence: 99%
“…Correct interpretation of blood culture results is one of the main responsibilities of the clinical microbiology laboratory for revealing the existence of these infections. For reducing mortality and morbidity rates, it is important to detect growing microorganisms in a short time, to find out whether they are causative agents or contaminants, and to direct the treatment properly by performing antibiotic susceptibility tests for the microorganisms accepted to be causative agents (1,2). Although various molecular methods, such as nucleic acid probes and polymerase chain reaction (PCR), have been developed for rapid diagnosis, blood culture is still the most sensitive and reliable method.…”
Section: Introductionmentioning
confidence: 99%